#TITLE_ALTERNATIVE# - WIDJAJA (S2-888807), WARKIANTO
Benkelman Beam deflection data, maximum deflection and surface curvature index, can be used as direct diagnostic parameters in evaluating the structural capacity of existing flexible pavements. A Backcalculation program using iterative precesses has been developed for evaluation of the structural capacity of flexible pavement from deflection parameters. The Backcalculation program applied in the calculation of modulus values of light flexible pavements in West Java using existing Benkelman Beam deflection and DCP data. The procedure used in the Backcalculation is as follows. The maximum deflection and surface curvature index values corresponding to assumed values of modulus are computed. The difference between the calculated and measured values of deflection parameters is assumed to be entirely due to the difference between assumed and actual modulus values. For a constant subgrade modulus, the pavement modulus is changed until the calculated and the measured deflection parameters match. The change increment in the pavement modulus is based on parabolic functions determined by the method of least squares. Two sets of modulus values are determined and treated as initial values for developing an iterative process using the Bisection method which is installed in the program. The Backcalculated modulus values compared with the DCP measured values and those calculated using the Hogg-Burmister and Rufford models. The Backcalculated modulus values tend to be lower than the values determined by the other methods, in particular those from DCP tests and the Rufford model. An analytical overlay design algorithm has been developed using as criteria the tensile strain on underside of asphalt layer and compressive vertical strain on top of subgrade Residual life of existing pavements was evaluated and most were found to be critical with regard to subgrade deformation. Overlay thickness were determined for existing pavement structures modelled on the basis of the modulus values. The resulting overlay thicknesses were compared with those calculated using the HRODI and TRRL methods. The calculated overlay thicknesses were generally greater than the values determined from HRODI and TRRL methods.